1997
DOI: 10.1007/s001250051435
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenetic role of impaired fatty acid trapping by adipocytes in generating the pleiotropic features of hyperapoB

Abstract: HyperapoB is the commonest dyslipoproteinaemia associated with coronary disease [1,2] and is characterized by an increased LDL particle number due to increased secretion of B100 lipoproteins by the liver [3]. The first feature of hyperapoB to be recognized was the elevated LDL particle number, many of which are smaller and denser than normal [4]. In reality, though, the metabolism of all the lipoprotein classes is demonstrably abnormal.At the onset, however, it must be appreciated that hyperapoB is a phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
8
2
Order By: Relevance
“…Another plausible mechanism by which plasma ApoB may predict inflammation is its ability to reflect the efficiency of fatty acid storage in adipose tissue [29]. Several types of fatty acids, like omega-6 [30], trans [31,32] and saturated fatty acids [32], have been shown to induce endothelial dysfunction and increased plasma concentration of CRP, IL-8, TNF-α, TNF-α-R2, adhesion molecules and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible mechanism by which plasma ApoB may predict inflammation is its ability to reflect the efficiency of fatty acid storage in adipose tissue [29]. Several types of fatty acids, like omega-6 [30], trans [31,32] and saturated fatty acids [32], have been shown to induce endothelial dysfunction and increased plasma concentration of CRP, IL-8, TNF-α, TNF-α-R2, adhesion molecules and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In FCHL patients, impaired ASP action has been held responsible for decreased uptake of postprandial FFA and consequently increased postprandial FFA flux to liver and VLDL overproduction, as seen in FCHL (30,31). The slightly higher fasting C3 concentrations, the precursor of ASP, in FCHL patients supports the theory of impaired ASP action (31). The slightly higher fasting C3 concentrations, the precursor of ASP, in FCHL patients supports the theory of impaired ASP action (31).…”
Section: Discussionmentioning
confidence: 68%
“…A recent study demonstrates that ASP increases in the venous effluent of a subcutaneous adipose tissue bed post-prandially [23]. Our hypothesis is that a reduced ASP receptor level results in reduced efficiency of fatty acid trapping by adipocytes in the post-prandial period [19]. Moreover, release of ASP by adipocytes increased markedly during the second half of the post-prandial period, during the marked increase in TG clearance and tissue uptake of fatty acid that occurred at that time.…”
Section: Discussionmentioning
confidence: 91%
“…Notwithstanding the elevated free fatty acids, hormonesensitive lipase-mediated release of adipose tissue free fatty acids is not increased but, in fact, is slightly decreased [18]. Based on these results we have postulated that the fundamental metabolic fault, in at least a subset of these patients, is a defect in the efficiency with which fatty acids are stored in adipocytes [19]. In support of this hypothesis, our initial studies in human skin fibroblasts in hyperapoB subjects demonstrated a reduced response to ASP stimulation of TGS in some, but not all, subjects [8].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation